DISTRIBUTION OF NATURAL RADIOACTIVE ELEMENTS IN THE HOLOCENE-PLEISTOCENE DEEP-WATER SEDIMENTS OF LAKE BAIKAL AND CHRONOLOGICAL CONSTRUCTIONS - Gavshin V.M.; Arkhipov S.A.; Bobrov V.A.; Mel'gunov M.S.; Makarova I.V.; Sukhorukov F.V.; Stepin A.S.; Khlystov O.M.; Kireev A.D.; Budashkina V.V. (My University, 1998)
In the Pleistocene-Holocene section of the Baikal deep-water sediments shales are periodically enriched with the siliceous shells of diatomic algae up to nearly pure diatomite. As the terrigenous shale-silty material is diluted with amorphous silica, the concentrations of all chemical elements, except for organic carbon and uranium, decrease in the sediments. As in seas and oceans, the blossom of diatomic algae in the Baikal basin is associated with the intensification of a supply of dissolved silica and nutrients under the climatic conditions close to the present-day ones, and the uranium concentration in the diatomic silts resulted from the formation of humic acids, which served as a precipitant. In the glacial periods, when erosion in the catch basins stopped, the contents of silicon, nitrogen, and phosphorus decreased below the level of their concentrations necessary for the vital activity of diatoms. That is why the diatom appearance in the section is a sign of paleoclimate. The diatomic muds, as compared with shales, are characterized by increased concentrations of U and reduced contents of Th; therefore, the Th/U ratio is a contrasting indicator of the chemical differentiation of the section. By configuration, the distribution curves for the Th/U ratio, biogenic silica, and organic carbon are consistent with the isotope-oxygen curves constructed on the chronological scale developed in detail in the last 20 years. This permitted establishment of the age boundaries of paleoclimatic epochs in the Baikal section, which are in good agreement with the chronostratigraphic constructions carried out by S. A. Arkhipov for the West-Siberian plain and are comparable with the West-European glaciation ages. Direct dating of the sediments by nonequilibrium uranium is hampered by the high content of terrigenous admixture in the diatomic silts and by the nonstationary initial 234U/238U ratio. It is shown that direct radiometric dating of the Baikal sediments will be favored by obtaining agreed age estimates by 234U and 230Th (or 226Ra).
Keywords: Pleistocene; Holocene; Cenozoic::Quaternary::Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Четвертичная::Голоцен